Complex impacts between economic policy and listed oil companies: a dynamics-based approach - Duan, Yanzhi; Jing, Xingsheng; Xu, Haitang; Wang, Zhong; Zhang, Xin; Wang, Yi (Frontiers in Physics, 2025)
The causal impacts between economic policy and listed oil companies have been discussed previously, reporting either positive or negative impacts. However, various channels bridge the impacts flowing between them, resulting in multiple causal impacts rather than only a single causal impact. This work employs a dynamics-based causality method, namely, pattern causality, and aims to reveal multiple causal interactions between economic policy and listed oil companies in China. Using the economics policy uncertainty index and the stock prices of nine popular listed oil companies in China from 2006 to 2025, several interesting findings are discovered. 1) Three kinds of causalities exist between economic policy and listed oil companies: positive, negative, and dark causality. Dark causality suggests more complex interactions, which may drive two variables to evolve with fluctuations; 2) rather than only one kind of causality, three heterogeneous causalities exist simultaneously with different magnitudes; 3) the causal impacts between the economic policy and listed oil companies are asymmetric; 4) by comparing the causal magnitudes, dark causality is shown to play a relatively dominant role between economic policy and listed oil companies. These new findings suggest complex interactions between economic policy and listed oil companies, requiring a reassessment of the underlying risks for market participants. Our approaches also offer an alternative perspective on understanding the complexity of social systems.